Optical wireless OFDM system on FPGA: Study of LED nonlinearity effects - Stefan, I; Elgala, H; Mesleh, R; O'Brien, D; Haas, H (2011)
Nonlinearities can drastically degrade the performance of OFDM (orthogonal frequency division multiplexing) based optical wireless (OW) communication systems using intensity modulation (IM) of the optical carrier. The light emitting diode (LED) transfer function distorts the signal amplitude and forces the lower signal peaks to be clipped at the LED turn-on voltage (TOV). Additionally, the upper signal peaks can result in optical output degradation. The induced distortion can be controlled by optimizing the bias point (BP) of the LED and/or backing-off the signal power modulating the LED. In this paper, the obtained experimental results using a hardware demonstrator for OW OFDM transmission based on field-programmable gate array (FPGA) and off-the-shelf analog components are presented. The conducted measurements for the bit-error performance focus on determining the optimum BP and optimizing the OFDM signal amplitude to obtain best performance. In this context, the experimental bit-error ratio (BER) is obtained as a function of the LED BP and the RMS (root mean square) OFDM signal across the LED. © 2011 IEEE.